Electrical design of Houbara Breeding Station Package II Rawdat Al Faraz, Qatar - Bugay, Jimmy Michael Y.
Houbara Breeding Station Package II Project aim is to preserve and reinforce populations of Houbara birds, and present in this report the electrical design and calculations with the main purpose to obtain a safe, economical and reliable power distribution system. The electrical design covers the sizing of switching devices ratings for power distribution (LV Panel, Submain Distribution Boards, Motor Control Center and Distribution Boards), cable sizing with consideration of voltage drop and determining rating of transformer, the author also provided in the design four prime rated 1875 kVA Generator set as a 100 % emergency backup with another back up to support two nos. 1600 kVA Transformer in case of normal power failure. Generator sets will serve alternately as normal power while commercial power is not yet available. Value engineering efforts were made by providing electrical room near to the loads it serve and applying diversity factor in total Maximum Demand Load to maximize transformer capacity. Final calculation results were obtained and used as basis for final selection of protective devices and settings, sizes of cables, determination of transformer rating and generator set ratings. After all the presented calculation and coordination study, it was concluded that the electrical design is safe with the specified materials able to handle/withstand the destructive short circuit current (high magnitude current). As discussed in recommendations and conclusion, the design engineer must not only consider sizing of protective devices, cables, switching device/equipment under normal conditions, rather consider the worst case scenario under abnormal condition of short circuit current. In sizing protective devices, it is not enough to specify the continuous current and voltage rating of a circuit breaker in preparing design, rather prepare protection coordination that will detect faults in the power system and isolate the fault portion of equipment from the healthy or unaffected portions of the power system to attain system reliability. Also, design engineer must rely on the performed protection coordination calculations settings not on the vendor/manufacturer's suggested settings of protective devices. For existing facilities, obtaining data is one of the challenges in performing short circuit calculations, protection coordination and the like. It is important to have as built drawings /updated records of data sheet in plants/facilities that will serve as reference in preparing electrical design, calculation and coordination study.